MR Cholangiopancreatography Versus Endoscopic Sonography in Suspected Common Bile Duct Lithiasis: A Prospective, Comparative Study - Aube, Christophe; Delorme, Benoit; Yzet, Thierry; Burtin, Pascal; Lebigot, Jerome; Pessaux, Patrick; Gondry-Jouet, Catherine; Boyer, Jean; Caron, Christine (American journal of roentgenology (1976), 2005)
Our purpose was to compare the accuracy of MR cholangiopancreatography and endoscopic sonography for the diagnosis of common bile duct stones in patients with a mild to moderate clinical suspicion of common bile duct stones. Forty-seven patients were prospectively enrolled. Inclusion criteria included acute pancreatitis, subclinical jaundice, and clinical features of common bile duct stone migration. Radial endoscopic sonography and MR cholangiopancreatography with the single-shot fast spin-echo technique were performed a maximum of 48 hr apart. The gold-standard diagnosis was obtained with ERCP (n = 20) or intraoperative cholangiography (n = 14) if the results of endoscopic sonography or MR cholangiopancreatography were abnormal or if a cholecystectomy was performed, or by clinical and biochemical follow-up (n = 11) if the results of endoscopic sonography and MR cholangiopancreatography were normal. The final diagnosis was common bile duct stones in 16 patients, malignant obstructions in four, and another biliary disease in two (lithiasis migration aspect with papillary edema); 23 patients had no biliary disease. The sensitivity and specificity of MR cholangiopancreatography were, respectively, 90.5% and 87.5% for etiologic diagnosis and 87.5% and 96.6% for the detection of common bile duct stones. The corresponding values for endoscopic sonography were 86.4% and 91.3% for etiologic diagnosis and 93.8% and 96.6% for visualization of choledocholithiasis. Accuracy did not significantly differ between the techniques. In cases of mild to moderate suspicion of choledocholithiasis, the accuracies of endoscopic sonography and MR cholangiopancreatography are similar. Because MR cholangiopancreatography is noninvasive, it may be preferred for this indication.